Pengenaan Pajak Penghasilan Terhadap Pelaku Usaha Jasa Promosi Melalui Media Sosial - Michael Lianwar Antolis; Ida Ayu Putu Widiati; I Putu Gede Seputra (Jurnal Interpretasi Hukum, 2021)
Income tax is a tax imposed on individuals/business entities on income earned in the tax year. Promotional service business actors are tax subjects who earn income that exceeds the non-taxable income and the income is obtained from activities promoting goods or services through social media, such as Instagram, YouTube, WhatsApp or other types of social media. The purposes of this study are to examine the regulation of income tax in promotional services business activities through social media as well as the mechanism for collecting income taxes against business actors in promotional services through social media. This study uses normative legal research methods, with legal materials consisting of primary legal materials and secondary legal materials. The collection of legal materials in this study was carried out by the recording method. The legal material analysis method used is argumentative technique. The result of the study shows that the regulation of income tax in promotional service business activities through social media, in this case YouTubers or Celebrities, is subject to income tax for those whose income exceeds Non-Taxable Income (PTKP) based on the Regulation of the Director General of Taxes Number PER-17/PJ/2015.